Optimization of Carbopol 940 Concentration in Bidara Laut Leaf Extract Anti-Acne Gel Preparations: Physical Stability and Inhibitory Effectiveness Study - Fhahri Mubarak; Nur Khairi; Dwi Tiva Widyanti S. Humolungo (Biology, Medicine, & Natural Product Chemistry, 2026)
Acne vulgaris is a widespread skin condition associated with Propionibacterium acnes, and conventional antibiotics often lead to resistance and irritation, underscoring the need for safer, natural therapies. This research explored the antibacterial potential of Strychnos ligustrina (Bidara Laut) leaf extract and its formulation into a topical gel. Leaves collected from Bima, West Nusa Tenggara, were processed into ethanol extracts, which were then screened for phytochemicals, confirming the presence of tannins and phenolics. Antibacterial activity was evaluated using disc diffusion at concentrations of 15%, 20%, and 25%, with clindamycin as the positive control and DMSO as the negative control. Gel formulations containing Carbopol 940 at concentrations of 0.5%, 1%, and 1.5% were prepared and evaluated for their physical properties, including organoleptic characteristics, homogeneity, pH, viscosity, spreadability, adhesion, and stability under accelerated storage conditions. The extract exhibited moderate inhibition of P. acnes, with the most substantial effect observed at a concentration of 25% (7.73 mm). Among the gel formulas, the 1.5% Carbopol gel (Formula 3) was the most stable and produced the largest inhibition zone (12.89 mm), although it was still lower than that of clindamycin (33.87 mm). Overall, the findings suggest that Bidara Laut extract can be formulated into a stable gel with measurable antibacterial activity, indicating its potential as a natural topical option for acne management. However, further refinement is needed to enhance its efficacy.